PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS ETNOMATEMATIKA CANDI JAWI PADA BANGUN RUANG SISI DATAR DI SEKOLAH MENENGAH PERTAMA (SMP) AL MUSTAQIM SUKOREJO PASURUAN - Azizah, Vivin Nor; ., Masrurotullaily (JURNAL MathEdu (Mathematic Education Journal), 2023)
Student worksheets are teaching materials in the form of sheets containing material and instructions for carrying out assignments as facilitators in the ongoing learning process. Student Worksheets can provide opportunities for students to construct conceptual understanding and practice creative thinking skills by playing an active role. This development model uses ADDIE (analysis, design, development, implementation and evaluation). This development research aims to: 1) Describe the process of developing student worksheets based on candi jawi ethnomathematics on the material of flat sided spaces at Al Mustaqim Middle School. 2) Knowing the quality of student worksheets resulting from three aspects, namely validity, practicality and effectiveness. The results of the product development research on student worksheets based on ethnomathematics candi jawi on the material of flat sided geometric shapes with due regard to appropriate competency standards and basic competencies. The results of the LKPD validation for each validator are 1) The average validation value for material experts is 3.5, 2) The average validation value for design experts is 3.9, 3) The average validation value for mathematics education experts is 4.3. And the total average value of the three validators is 4.23 with very valid criteria. The average result of the score from the teacher and student response questionnaire in the practicality test was 4 for educator responses and 4.046 for student responses with practical criteria. And the average result of the test score of the 5 essay questions in the effectiveness test is 80% with the complete criteria, so that the LKPD developed reaches the criteria for being effective. Keywords: Student Worksheets, Ethnomathematics, Candi Jawi, Building Flat Sided Spaces.